2022
DOI: 10.1111/hsc.13917
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between parent–infant bonding, dyadic adjustment and quality of life, in an intra‐partner sample

Abstract: According to the family systems theory, the family is characterised by a hierarchical structure (i.e., it is composed of subsystems that are systems in and of themselves) and adaptive self-organisation able to adjust to change or challenges (Cox & Paley, 2003). The transition to parenthood represents a moment of change for couples at both the intra-personal and inter-personal levels. The term 'transition' is defined as a temporary process during which people must adapt to a new situation (Kralik et al., 2006) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
2
1
1
Order By: Relevance
“…Consistent with previous studies, the mothers' levels of FSOC, marital satisfaction, and parent-infant bonding were closely related to those of their partners 26,33–35. Furthermore, the present findings showed that the marital satisfaction of both parents was influenced by their sense of family coherence and that of their partners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, the mothers' levels of FSOC, marital satisfaction, and parent-infant bonding were closely related to those of their partners 26,33–35. Furthermore, the present findings showed that the marital satisfaction of both parents was influenced by their sense of family coherence and that of their partners.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, the mothers' levels of FSOC, marital satisfaction, and parent-infant bonding were closely related to those of their partners. 26,[33][34][35] Furthermore, the present findings showed that the marital satisfaction of both parents was influenced by their sense of family coherence and that of their partners. Given the close relationships between family members in Chinese society, 36 it is likely that the parents in this study shared experiences on their sense of family coherence, marital satisfaction, and parent-infant bonding, which might have had reciprocal effects.…”
Section: Limitationssupporting
confidence: 53%
“…Parents' bonding with their baby tends to be similar [73], indicating no differences between the sexes. However, some studies [76,77] have found that mothers have better bonding scores, indicating less concern for a lack of postpartum bonding among mothers compared to fathers, whereas Ngai and Lam (2023) found that mothers have more difficulties in bonding with their baby compared to fathers [38]. Based on the data of this study, it is not possible to confirm or deny the difference between the primiparae's and spouses' bonding with their baby.…”
Section: Discussioncontrasting
confidence: 59%
“…In a study on parenting and the role of fathers, it is essential to consider the cultural characteristics of the sample. Culturally, fathers are more involved in household responsibilities and childcare in Spain, compared to cultures with more traditional family models where the caring role falls mainly on mothers, as described elsewhere (Escribano et al, 2022).…”
Section: Setting and Relevant Contextmentioning
confidence: 99%